Preservation And Conservation Library Material Activities In Library Of State Islamic University Of North Sumatra (UINSU) - Gustia, Putri; Nurhayani; Purwaningtyas, Franindya (Pena Cendekia Insani, 2022)
This research discusses the preservation and conservation of library materials at the North Sumatra State Islamic University Library. The objectives of this research are:Knowing how the activities of preservation and conservation of library materials in the Library of the State Islamic University of North Sumatra. Knowing what are the obstacles in carrying out preservation and conservation of library materials at the North Sumatra State Islamic University Library. This research method uses a qualitative descriptive approach. By using data collection techniques through interviews, observation and documentation. The informants in this study were the head of the library and librarian at the North Sumatra State Islamic University Library who had been selected by the researcher in accordance with the criteria for the research subject. The results showed that the factors causing damage to library materials at the Library of the State Islamic University of North Sumatra were: biological factors, physical factors, natural disaster factors and human factors or external and internal factors. The precautions taken to prevent further damage to library materials are: Cleaning and providing camphor in the bookshelves so as not to be eaten by insects, and users are also prohibited from bringing food into the library and smoking in the library is prohibited because it can endanger library materials. The constraints faced by librarians in preserving and conserving library materials are: Lack of awareness of students results in damaged library materials and damaged cover rights that can no longer be sewn and salasiban, and the lack of proper implementation of mangement for librarians. As for some suggestions given by researchers, among others: To prevent damage to library materials, libraries should work together with students so that students visiting the library can keep the library materials read well and do not tear and cross library materials.